Good risks : discovering the secrets to ORIX's 50 years of success - Russell, David, 1952- (Wiley, 2014)
Get inside Japan's invisible behemoth to see the future of global business Good Risks is a fascinating insight into ORIX, a global giant whose business empire straddles the world, but which has managed to remain out of the media spotlight for half a century. Award winning author David Russell explains how this Japanese company has transcended its national identity to become a global player, and what that means for everyone else. In a series of one-on-one interviews with senior executives at ORIX companies around the world, readers gain a firsthand glimpse of the inner workings of this "invisible" corporate group that controls hundreds of billions of dollars. Interviews with the company President and Chairman in Tokyo provide rare insight into the thought leaders at the highest levels, and a contribution by the Chairman himself discusses the hard realities of globalization and the keys to success in the coming decade. The key concept that is lost in the Japan vs. China vs. US vs. EU battle is that the business landscape has changed drastically, making national boundaries anachronistic. Companies such as IBM, Disney, Apple, and Microsoft long ago stopped being "American" firms; they are global competitors that take advantage of their deep knowledge of the US markets, but have no special allegiance to the United States. This book argues that this is the future of all large-scale business, as already exemplified by ORIX. -Learn how one executive steered ORIX's meteoric rise from an unknown start-up to an unseen global giant -Explore the coming realities of the global business scene -Discover why HQ location will be little more than historical accident -See how ORIX impacts the Chinese, Indian, and American firms that follow its lead The business scene unfolding today is not "international" or "multinational", but an increasingly unified, global battleground. The rise of ORIX charts the future of business, and Good Risks provides the details and insights business leaders need to anticipate tomorrow's changes.